The Impact of Behavioral Intention on Financial Technology in Banking Sector - Rasyidin, M; Anwar Puteh; Zulfikar; Al Mahfud Saputra; Hakim Muttaqim; Azka Rizkina (Forum Kerjasama Pendidikan Tinggi, 2025)
This study examines behavioral intention indicators towards financial technology in the Islamic banking sector in Indonesia. Behavioral intention indicators consist of belief in outcomes and Commitment to Act. This study uses a quantitative approach. Purposive sampling technique was used, resulting in a sample size of 383 participants, selected through the Unknown Populations method. Data were collected through questionnaires distributed via Google Forms. In this study, the population consists of banking service users who have interacted with financial technology. The criteria established include individuals aged 18 and above who have used financial technology products or services within the last six months. The research location is selected in Indonesia, conducted from January to May 2025. The analysis carried out includes validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, and regression analysis tests (ANOVA). The model used is multiple linear regression analysis. The results of the study indicate that belief in outcomes has a positive and significant effect on financial technology, while commitment to act also has a positive and significant effect on this financial technology.